Signalling scheme for achieving dynamic degrees of freedom in MIMO Y channel. (1st January 2014) - Wang, Yong; Guo, Aixiang; He, Hong; Li, Hui; Li, Fengrong
The Multiple Input and Multiple Output (MIMO) Y channel is a generalised channel model of the two-way relay channel, which supports point-to-multipoint traffic pattern for unicast. In this paper, a signalling scheme for achieving dynamic Degrees of Freedom (DOF) in the MIMO Y channel is proposed where each user exchanges d pairs of messages with each of the other users simultaneously via an intermediate relay and d is a variable integer. To complete this scheme, two novel signalling techniques are utilised, which are Signal Space Alignment for Network Coding (SSA-NC) and interference nulling beamforming combined with Receiving Antenna Selection (RAS) technique. Dynamic DOF can be obtained by changing d, e.g., more diversity gain can be obtained if d is small, while more DOF can be achieved if d becomes larger.